Current status of Panton–Valentine leukocidin‐positive methicillin‐resistant Staphylococcus aureus isolated from patients with skin and soft tissue infections in Japan. Issue 11 (21st July 2020) - Nakaminami, Hidemasa; Ozawa, Kazuya; Sasai, Nao; Ikeda, Masami; Nemoto, Osamu; Baba, Naoko; Matsuzaki, Yasushi; Sawamura, Daisuke; Shimoe, Fumiko; Inaba, Yoichi; Kobayashi, Yoko; Kawasaki, Satoru; et al.
Abstract: The USA300 clone, which produces Panton–Valentine leukocidin (PVL), is a major pathogenic community‐acquired methicillin‐resistant Staphylococcus aureus (CA‐MRSA) clone that causes intractable skin infections. Recently, PVL‐positive CA‐MRSA, including USA300 clones, have emerged in both communities and hospitals in Japan. To prevent an outbreak of PVL‐positive MRSA, infected patients should be treated with effective antimicrobial agents at community clinics. Herein, we investigate molecular epidemiological characteristics of PVL‐positive MRSA isolated from outpatients with skin and soft tissue infections (SSTI), which are common community‐onset infectious diseases. The detection rate of MRSA was 24.9% (362 strains) out of 1455 S. aureus strains isolated between 2013 and 2017. Among the MRSA strains, 15.5% (56 strains) were PVL‐positive strains and associated with deep‐seated skin infections. Molecular epidemiological analyses of PVL‐positive MRSA showed that USA300 was the predominant clone (53.6%, 30 strains) and was identified in Kanto (18 strains), Kagawa (nine strains), Tohoku (two strains) and Hokkaido (one strain). Notably, minocycline and fusidic acid were effective against all PVL‐positive MRSA strains. Hence, our data reveals the current status of PVL‐positive MRSA isolated from patients with SSTI in Japan. Continuous surveillance of CA‐MRSA is necessary to monitor latest prevalence rates and identify effective antimicrobial agents for PVL‐positive MRSA strains.